Hypertrophic and Dilated Cardiomyopathy-Associated Troponin T Mutations R130C and ΔK210 Oppositely Affect Length-Dependent Calcium Sensitivity of Force Generation - Groen, Marcel; López-Dávila, Alfredo Jesus; Zittrich, Stefan; Pfitzer, Gabriele; Stehle, Robert (Frontiers in Physiology, 2020)
Length-dependent activation of calcium-dependent myocardial force generation provides the basis for the Frank-Starling mechanism. To directly compare the effects of mutations associated with hypertrophic cardiomyopathy and dilated cardiomyopathy, the native troponin complex in skinned trabecular fibers of guinea pigs was exchanged with recombinant heterotrimeric, human, cardiac troponin complexes containing different human cardiac troponin T subunits (hcTnT): hypertrophic cardiomyopathy-associated hcTnT-R130C, dilated cardiomyopathy-associated hcTnT-dK210 or the wildtype hcTnT (hcTnT-WT) serving as control. Force-calcium relations of exchanged fibers were explored at short fiber length defined as 110 % of slack length (L0) and long fiber length defined as 125 % of L0 (1.25 L0). At short fiber length (1.1 L0), calcium sensitivity of force generation expressed by –log [Ca2+] required for half-maximum force generation (pCa50) was highest for the hypertrophic cardiomyopathy-associated mutation R130C (5.657+/-0.019), intermediate for the wildtype control (5.580+/-0.028) and lowest for the dilated cardiomyopathy-associated mutation dK210 (5.325+/-0.038). Lengthening fibers from 1.1 L0 to 1.25 L0 increased calcium sensitivity in fibers containing hcTnTR130C (delta-pCa50 = +0.030+/-0.010), did not alter calcium sensitivity in the wildtype control (delta-pCa50 = -0.001+/-0.010), and decreased calcium sensitivity in fibers containing hcTnTK210 (delta-pCa50 = 0.034+/-0.013). Length-dependent activation indicated by the delta-pCa50 was highly significantly (P<0.001) different between the two mutations. We hypothesize that primary effects of mutations on length-dependent activation contribute to the development of the diverging phenotypes in hypertrophic and dilated cardiomyopathy.